Fission cross section measurements with the MicroMegas detector - Diakaki, M.; Kokkoris, M.; Kyrtsos, A.; Skordis, E.; Vlastou, R.; Andriamonje, S.; Berthoumieux, E.; Lagoyannis, A. (HNPS Advances in Nuclear Physics, 2019)
A new MicroMegas detector, based on the innovative Microbulk technology, especially developed within the context of the n TOF collaboration, was used for the first time for fission cross section measurements with monoenergetic neutron beams at the Institute of Nuclear and Particle Physics of the NCSR “Demokritos”. The detector assembly was successfully used in the case of the measurement of the 237Np(n,f) cross section while the first results on the performance of the detector as far as the gain and resolution function are concerned are reported.